Coexisting cystic lesions with right-sided congenital diaphragmatic hernia in a neonate - Debasish Nanda; Antaryami Pradhan (Journal of Indian Association of Pediatric Surgeons, 2022)
Diaphragmatic defects involving the right side of the diaphragm are less common but represent a distinct entity. The clinical presentation, management, and prognosis differ significantly from a left-sided defect. We report a case of a term neonate who was diagnosed to have a congenital diaphragmatic hernia during the third trimester of pregnancy, operated at 36 h of life and subsequently found to have an associated mediastinal cyst in 1st week of life.